“Out of Africa”: Racist discourse in men’s talk on sex work - Huysamen, Monique; Boonzaier, Floretta (PINS-Psychology in Society, 2018)
Sex work remains highly stigmatised throughout the world. This is particularly true in South Africa, where legal, academic, and popular discourses continue to construct sex workers and their clients as responsible for the spread of HIV/AIDS, thereby exacerbating the public panic and stigma related to sex work. Through the lenses of feminist decolonial and queer theories, this paper explores how male clients manage the stigma associated with the purchase of sex and how they negotiate their gendered identities by enlisting discourses of race and class. Drawing on excerpts from in-depth interviews with 43 men who identify as clients of women sex workers, we show how men evoked racist colonial tropes to construct the black body as lower class, dirty and diseased. We argue that this denigration of the black Other allowed men to construct their own masculine identities favourably. To conclude, we reflect upon how legislation that criminalises sex work in South Africa operates in tandem with structural inequalities and racist ideologies to maintain and perpetuate the stigmatisation of the black body, particularly the black woman sex worker.